Entre as trajetórias escolares e as práticas pedagógicas: as percepções dos professores na perspectiva da relação com o saber - Idem, Fabiano Donizeti (Universidade Federal de São Carlos, 2024)
Pedagogical practices and school background play crucial roles in teacher training, profoundly influencing their educational approaches and teaching methods. Teachers' school careers, including their experiences and memories when they were primary school students, shape their perceptions and attitudes towards the teaching-learning process. These formative experiences serve as a reference for the construction of their professional and epistemological identities. With this in mind, the aim of this study was to understand the perceptions of 9th grade elementary school teachers about the relationship between their school trajectories and their teaching practices. To this end, the study was qualitative and exploratory in nature, and did not start from an initial hypothesis. A social constructivist approach was also adopted, as it is understood that subjects develop varied, multiple, subjective and social meanings of their experiences. Two data collection instruments were used: a questionnaire characterizing the participants and with open-ended questions about their perception of their school career, teaching practices and the role of education, the school and the teacher today; and a semi-structured interview about their school career, the description of their own teaching practices, how these add to the practices with which the subject-teachers were trained, their perception of what they still retain from the school where they studied, the relationship between their school career and teaching practices and, finally, the epistemic relationship that the subject-teacher maintains with the curricular component they teach. Five 9th grade elementary school teachers from a school in the city of Descalvado took part in the research. The data was analyzed from the theoretical perspective of Bernard Charlot's Relationship with Knowledge: the questionnaires were analyzed based on the Balance of Knowledge, adapted for this research by constructing mind maps; and the interviews were analyzed based on the QCC Matrix (When student, As teacher and With students), constructed for this research. This analysis was based on three categories identified in the interviews: a student model; from perception to a new conception of the student-subject (both from a diachronic perspective); and the knowledge of the trajectory and professional performance, from a synchronic perspective of the teacher's action in the pedagogical relationship. The analyses showed that, when they were students, they prioritized only the cognitive aspect of the student. However, the conception that these teachers adopt of the student-subject reflects a holistic and integrative vision, recognizing them in their totality and complexity, in other words, from the cognitive, emotional, social and cultural dimensions. By revisiting their school career, it was possible to see how the memories of the teacher-subjects are constantly revisited and used as practical references in the current school environment, improving teaching approaches and avoiding repeating patterns that may not have been effective or inspiring during their own school experience. In this way, it was possible to identify the existence of an epistemology of trajectory, understood and conceived as the study of the knowledge acquired by teachers throughout their school careers, especially from the time they were primary school students, and its relationship with teaching practice. The epistemology of trajectory maintains the appreciation of tacit and practical knowledge from Maurice Tardif's epistemology of practice, but adds a temporal and biographical dimension, showing that the construction of knowledge is a continuous and relational process that extends beyond the university context and the immediate classroom. In this interweaving of times and experiences lies the true essence of education: a continuous construction of meaning, where each life trajectory becomes an indispensable chapter in the great narrative of learning and teaching.
Between school trajectories and pedagogical practices: teachers' perceptions from the perspective of the relationship with knowledge
Keywords: Relação com o saber; Percepção dos professores; Trajetória escolar; Práticas pedagógicas; Epistemologia da trajetória; Relationship with knowledge; Teachers' perceptions; School trajectory; Pedagogical practices; Epistemology of the trajectory; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO